Finite element analysis of necessity of reduction and selection of internal fixation for valgus-impacted femoral neck fracture. Issue 7 (19th May 2023) - Dai, Yahui; Ni, Ming; Dou, Bang; Wang, Zhiyuan; Zhang, Yushan; Cui, Xueliang; Ma, Wenqian; Qin, Tao; Xu, Xiaobin; Mei, Jiong
Abstract: This study compared the biomechanical characteristics of different treatment strategies based on finite element analysis. Posterior tilt and valgus angle were measured on X-ray from ten valgus-impacted femoral neck fractures, and 7 finite element models that were generated to compare the stress and displacement. The results showed that in the intact femur, von Mises stress was concentrated at the medial and inferior sides of the femoral neck. In valgus-impacted femoral neck fractures, von Mises stress was at the same locations but was 5.66 times higher than that in the intact femur. When 3 cannulated screws were used for internal fixation, anatomic reduction diminished the stress at the fracture end from 140.6 to 59.14 MPa, although displacement increased from 0.228 to 0.450 mm. When the fracture was fixed with a sliding hip screw (SHS) + cannulated screw, there was less stress at the fracture end and greater displacement with anatomic reduction than that without reduction (stress: 15.9 vs 37.9 MPa; displacement: 0.329 vs 0.168 mm). Therefore, the SHS + cannulated screw has superior biomechanical stability than 3 cannulated screws, and is recommended following anatomic reduction to treat valgus-compacted femoral neck fractures.